PEMBERDAYAAN KELUARGA DALAM MERAWAT ANGGOTA KELUARGA YANG MENGALAMI GANGGUAN JIWA WILAYAH KERJA PUSKESMAS SUKAMERANG GARUT - Tanti Suryawantie; Ishmah hamidah; Rifa Aulia A Lubis (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
The family is the most important part in the recovery process in patients withmental disorders. The family plays a role in carrying out care at home, providingmental support, economics and other needs needed by other family members whoexperience mental disorders. The successful recovery of people with mentaldisorders (ODGJ) depends on the care and ability of the family to provideappropriate assistance. Based on the results of Iskandar et al's research (2022) atthe Sukamerang Health Center, Garut Regency, it was stated that the function ofthe family in maintaining the health of a family member who has a mentaldisorder is not supportive. Therefore, sufficient knowledge and skills are neededin managing the dynamics of family psychology while providing assistance. forODGJ. The purpose of this community service is to increase the knowledge andmentality of the ODGJ family. The method used is pre and post tests related to the material then followed by the lecture method related to mental disorders material,ways of accompaniment, how to communicate with ODGJ, managing stress andhow to deal with stigma about ODGJ. The results of this community service arean increase in knowledge before and after counseling. It is hoped that thiscommunity service will increase the knowledge and mentality of the family incaring for family members who have mental disorders